Microscopic and macroscopic anatomical features in healthy and osteoarthritic knee cartilage. Issue 3 (2013) - Musumeci, G; Castrogiovanni, P; Trovato, FM; Giunta, A Di; Loreto, C; Castorina, S
No abstract available